Internal Brand Communication Strategies for Lecturer Engagement in the Digital Era - Dewiana Novitasari; Yunianto Agung Nugroho; Yulis Nuryanti; Masduki Asbari (Edumaspul: Jurnal Pendidikan, 2024)
This study examines the relationship between internal brand management (IBM) consisting of internal brand communication (IBC), brand-centered training (BCT) and transformational leadership (TL) on work engagement (WE) at a university in Jakarta. A model was proposed and tested using a sample of 250 home-based lecturers using simple random sampling technique. Data were analyzed with SEM PLS and SmartPLS 4.0 software. The findings of this study confirm that internal brand communication, brand-centered training and transformational leadership positively influence work engagement. The results of this study also show that internal brand communication, brand-centered training and transformational leadership are good predictors of work engagement of lecturers in higher education. The implication is that the combined effects of internal brand communication, brand-centered training, and transformational leadership can create a work environment where lecturers are connected to the organization, motivated to contribute to its success, and engaged in the role of the campus brand. By prioritizing these factors, university management can foster a culture of engagement, commitment, and alignment with the university brand image, which ultimately leads to improved performance and satisfaction of all university stakeholders.